2015
DOI: 10.1016/j.cct.2014.11.011
|View full text |Cite
|
Sign up to set email alerts
|

Design and implementation of a study evaluating extinction processes to food cues in obese children: The Intervention for Regulations of Cues Trial (iROC)

Abstract: Obesity and its health sequelae affect a significant portion of children in the United States. Yet, the current gold-standard family-based behavioral weight-loss treatments are only effective for one-third of children long-term. Therefore, we developed iROC (Intervention for Regulation of Cues) to specifically target a method to decrease overeating in overweight children, based on learning theory, to inform and enhance interventions targeting diet and obesity in youth. This study will rigorously test extinctio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 71 publications
0
7
0
Order By: Relevance
“…Typical onset of obesity in adulthood is a slow, incremental process (Christiansen, Swann, & Sorensen, 2008), and while a few dozen additional calories at a given meal may not seem substantial, individuals prone to eat 50 kcal more per day will end up approximately 50 lb heavier than their counterparts after ten years. Targeting reward sensitivity through cue-exposure paradigms (Boutelle et al, 2015) or DD through interventions designed to boost ability to delay gratification (Daniel, Stanton, & Epstein, 2013) may be useful in preventing weight gain.…”
Section: Discussionmentioning
confidence: 99%
“…Typical onset of obesity in adulthood is a slow, incremental process (Christiansen, Swann, & Sorensen, 2008), and while a few dozen additional calories at a given meal may not seem substantial, individuals prone to eat 50 kcal more per day will end up approximately 50 lb heavier than their counterparts after ten years. Targeting reward sensitivity through cue-exposure paradigms (Boutelle et al, 2015) or DD through interventions designed to boost ability to delay gratification (Daniel, Stanton, & Epstein, 2013) may be useful in preventing weight gain.…”
Section: Discussionmentioning
confidence: 99%
“…We are in the process of developing a “cue-exposure treatment” for food (CET-Food) for overweight and obese children (Boutelle et al, 2011; Boutelle, N. Zucker, et al, 2014; Boutelle, Liang, et al, 2014). These methods were initially described decades ago in a pilot trial which showed that cue-exposure treatment led to abstinence as compared to self-control training with adults who binge eat and/or have bulimia nervosa (Jansen, Broekmate, & Heymans, 1992).…”
Section: Using Learning Theory To Reduce Food Cue Reactivitymentioning
confidence: 99%
“…Following the exposure session, the food is thrown away in a trashcan. Initial pilot studies suggest that CET-Food shows some efficacy in decreasing overeating in overweight and obese children (Boutelle et al, 2011) and we are currently in the process of conducting a series of studies based on extinction theory to enhance CET-Food with children (Boutelle, Liang, et al, 2014). Additionally, recent data suggest that this method may also have promise with adults.…”
Section: Using Learning Theory To Reduce Food Cue Reactivitymentioning
confidence: 99%
“…For example, the stability of EAH as measured by questionnaire has been explored in older children (Tanofsky-Kraff et al, 2008), but to our knowledge no studies have evaluated the stability in observed EAH across time, particularly in very young children (Lansigan et al, 2015), which is a unique contribution of the current study. Our finding that EAH emerges early in the lifespan and remains moderately stable also suggests that childhood obesity prevention efforts that focus on EAH (Boutelle et al, 2015) should begin as early as possible.…”
Section: Discussionmentioning
confidence: 58%